2010
DOI: 10.15420/ecr.2010.8.2.40
|View full text |Cite
|
Sign up to set email alerts
|

Drug Release Profiles of Different Drug-coated Balloon Platforms

Abstract: Drug-coated balloons are a new tool for the treatment of de novo or in-stent stenosis; as yet little is known about the principle by which these devices apply their therapeutic agents during intervention. Concerns remain regarding clinical safety and efficacy of different coatings, mainly influenced by the amount of drug transferred into the arterial tissue and lost into the bloodstream. To assess whether the chemical or mechanical set-up influences drug migration and wash-off, we compared four paclitaxel-coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 8 publications
1
22
1
Order By: Relevance
“…Most of these carriers are chosen on the basis of their usefulness to improve drug penetration into the tissue and not on whether they assist in delivering significant amount of drug at the treatment site of diseased portion of the artery. The major limitation of currently available DCBs is the delivery of drug from the balloons is not controlled effectively in order to avoid drug loss during balloon tracking and to rapidly deliver a therapeutic level of drug at the treatment site [11][12][13][14]. It has been reported that a significant amount of drug (up to 80%) is lost in the blood stream even before the balloon is tracked to the treatment site [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these carriers are chosen on the basis of their usefulness to improve drug penetration into the tissue and not on whether they assist in delivering significant amount of drug at the treatment site of diseased portion of the artery. The major limitation of currently available DCBs is the delivery of drug from the balloons is not controlled effectively in order to avoid drug loss during balloon tracking and to rapidly deliver a therapeutic level of drug at the treatment site [11][12][13][14]. It has been reported that a significant amount of drug (up to 80%) is lost in the blood stream even before the balloon is tracked to the treatment site [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The major limitation of currently available DCBs is the delivery of drug from the balloons is not controlled effectively in order to avoid drug loss during balloon tracking and to rapidly deliver a therapeutic level of drug at the treatment site [11][12][13][14]. It has been reported that a significant amount of drug (up to 80%) is lost in the blood stream even before the balloon is tracked to the treatment site [11][12][13][14]. Also, during the short balloon inflation time (2 to 3 min), the drug is not rapidly transferred from the balloon to the tissue [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carriers, mostly hydrophilic structures, try to minimize the loss of the hydrophobic paclitaxel microparticles in the systemic circulation (19). The inflation time is as important as the efficacy of the carrier to reach therapeutic levels of paclitaxel in the target lesion (20).…”
Section: Discussionmentioning
confidence: 99%
“…25 Heilmann et al had found (via an in vivo study) that the advantageous effect of a hydrophilic additive such as using iopromide for higher tissue concentrations was antagonized by increased amounts of wash-off of used coatings. 26 Drug loss is a process constituted of mechanical loss by sheath passage and collisions with the vessel wall and dissolution of the coating in the blood stream. 26 This process will be simulated using a standard anatomic model adapted from ASTM F2394-07 (described in next section).…”
Section: Comparison Of Different Hydrogels In the Ow-through Cellmentioning
confidence: 99%